A new dioecious species of Begonia (Begoniaceae) from Arunachal Pradesh, India - Das, Bikas; Saikia, Jadumoni; Konwar, Parthapratim; Siga, Appu; Banik, Dipanwita (Phytotaxa, 2022)
A new species, Begonia dalaiensis (sect. Platycentrum) is described from Arunachal Pradesh, Northeast India. A morphological description along with a photographic plate, distribution map and conservation status is provided here. The phylogenetic relationship among the allied species of this section is also established here based on molecular evidence.